2022
DOI: 10.3390/molecules27206868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acids on Folates Accumulation in Wheat Seedlings during Germination under Red Light Radiation

Abstract: Deficiency of folates can cause various health problems, and germination is a potential way to enrich folates in grain-based food materials. In the present study, the effects of six amino acids (phenylalanine, tyrosine, tryptophan, glutamate, γ-aminobutyric acid, and p-aminobenzoic acid) on folate accumulation during wheat germination under red light radiation were investigated, and an optimized combination of amino acids for promoting folate enrichment was established. The results showed that applying phenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…THF, 5-CH 3 -THF, and 10-CHO-THF can be oxidized into FA, MeFox, and 10-CHO-FA, respectively . MeFox has also been found in raw legumes such as soybeans, lentils, chickpeas, and peas and cereals like wheat germ and oat flour . Similarly, our present study found that the content of MeFox was quite high.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…THF, 5-CH 3 -THF, and 10-CHO-THF can be oxidized into FA, MeFox, and 10-CHO-FA, respectively . MeFox has also been found in raw legumes such as soybeans, lentils, chickpeas, and peas and cereals like wheat germ and oat flour . Similarly, our present study found that the content of MeFox was quite high.…”
Section: Resultssupporting
confidence: 81%
“…31 MeFox has also been found in raw legumes such as soybeans, lentils, chickpeas, and peas 30 and cereals like wheat germ and oat flour. 18 Similarly, our present study found that the content of MeFox was quite high. As shown in Figure 1B(g,h), in quinoa seeds of LL-1, QL-2, and GZ-4, the ratios of the oxidation product MeFox to 5-CH 3 -THF were 329.5, 122.9, and 226.5%, respectively, while the proportion of MeFox to 5-CH 3 -THF decreased to 33.6, 20.2, and 51.1% in 6-day-old quinoa sprouts of LL-1, QL-2, and GZ-4, respectively.…”
Section: Effects Of Germination On Accumulation Of Folatesupporting
confidence: 81%
See 3 more Smart Citations